Zircon double-dating of quaternary eruptions on Jeju Island, South Korea - Marsden, Ruby C.; Danišík, Martin; Ahn, Ung San; Friedrichs, Bjarne; Schmitt, Axel Karl; Kirkland, Christopher L.; McDonald, Bradley J.; Evans, Noreen J. (Journal of volcanology and geothermal research, 2021)
Models of volcanic eruption periodicity are vital for hazard prediction, but require an understanding of the past pattern of melt evolution and transport. Zircon double-dating combines (U-Th)/He methods with U-Pb or U-Th disequilibrium geochronology to determine the timing of volcanic eruptions for rocks with a particular emphasis on those younger than ca. 1 Ma. This paper focuses on the Jeju Island intraplate volcano in South Korea, and compares a previously proposed model for trachyte eruption with new zircon double-dating results. The results document four episodes of trachyte eruption on Jeju. The oldest trachytes were erupted at ca. 750-477 ka, followed by an episode at ca. 97-53 ka. Two further eruptive episodes occurred at ca. 31-23 ka and ca. 2 ka. This ca. 2 ka eruption age is the first geochronological documentation of such young eruptive activity from the island. In addition to the new eruption ages, there is evidence for three separate stages of zircon crystallisation, which are correlated with the three oldest eruption stages. The strong temporal correlation of zircon crystallisation and eruption on Jeju points to a simple magmatic plumbing system. These observations have important implications for hazard monitoring and mitigation on Jeju Island by highlighting the historical trachyte eruptions and the magmatic tempo for this system.